(untitled) (Research, Society and Development, 2025)
The climacteric is the natural transition from the reproductive to the non-reproductive phase in women, beginning around the age of 40 and culminating in menopause, the permanent cessation of menstruation. This period is characterized by various physiological and psychological symptoms, as well as significant social changes. The aim of this study was to understand the biopsychosocial aspects experienced by women during the climacteric. To achieve this, an integrative literature review method was adopted, selecting articles published between 2014 and 2024 in Portuguese, English, and Spanish, based on combinations of the following descriptors: Climacteric, menstruation, menopause; models, biopsychosocial and women. Data collected from the SciELO, LILACS, PubMed, and ScienceDirect databases were organized and analyzed using Bardin’s content analysis method. After reading and analyzing the selected works, four thematic categories were identified: 1) The lack of knowledge and preparation in women for experiencing the climacteric; 2) The impacts of climacteric symptoms on daily life; 3) The climacteric as a marker of female aging; 4) Strategies for adaptation and treatment used during the climacteric. The results allowed the conclusion that this phase is often faced without proper knowledge and that the topic is still surrounded by taboos related to aging and myths. Furthermore, the characteristic symptoms of the climacteric significantly impact the lives of many women, causing suffering and affecting various aspects of daily life.